The influence of low self-control, fear of missing out online reviews, hedonic motivations, materialism, and price value on impulsive buying through impulsiveness of social networks and positive attitude toward targeted advertising among young Shopee consumers in Indonesia - Falajunah, Cut Tamara; Dewi, Citra Kusuma (Edelweiss Applied Science and Technology, 2025)
This study explores the phenomenon of impulsive buying among Generation Z Shopee users in Indonesia, focusing on the influence of psychological and social factors. A quantitative, causal research design was employed, with data collected from 300 respondents through an online survey. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 to evaluate both the measurement and structural models, ensuring the validity and reliability of the instruments. The findings reveal that low self-control, fear of missing out (FOMO), and materialism significantly influence impulsive buying behavior. Social network impulsiveness and positive attitudes toward targeted advertising served as important mediators. Hedonic motivation, online reviews, and perceived price value also had substantial effects, although FOMO and perceived price value were not directly significant. Digital media plays a crucial role in shaping impulsive buying behavior, with internal psychological factors amplifying these effects through social media platforms and personalized advertisements. This research offers valuable insights for marketers targeting Generation Z consumers, emphasizing the need for responsible advertising that accounts for psychological triggers. It also underscores the importance of digital literacy and emotional regulation in consumer decision-making.